POLYANILINE MATRIX AS ACTIVE LAYER FOR SENSORS - P.D, GAIKWAD; V.P, SANGALE (Innovare Journal of Sciences, 2020)
Objective: Conducting polymer has gained importance due to its environmental stability, good conductivity, immobilization of bio component and gas sensing ability. Objective to Synthesis ofconducting polymers and to fabricate by galvano-static method for sensors. Material and method: All the chemical (Aniline and Hydrochloric acid)used in the investigation were analytical reagent grade The Method is electro polymerization was carried out by Galvanostatic technique. after synthesis, polymer coated electrodes were rinsed thoroughly in distilled water and dried in cold air and then used for subsequent characterization. Results: Potential-time curves suggesting that building up of the film proceeds according to the same reaction along the full thickness of the polymer. The SEM micrograph is fibrillar like structure good porosity, Conclusions: The PANI-HCl matrix have been successfully synthesized using Galvanostatic Method on ITO glass plate has uniform matrix and conductivity which has porous and fibriller good porosity and conductivity this active layer is suitable for immobilization of biocomponet for biosensors ,gas sensors and opticalsensors